The meta-analysis study: career decision making self efficacy and career maturity - Abdullah, Sri Muliati (Universitas Mercu Buana Yogyakarta, 2023)
This study was a meta-analysis of the relationship between Career Decision Making Self Efficacy and Career Maturity. Career maturity is one of the most important and interesting issues among student or undergraduate career development. The quantitative review of primary studies from 11 studies examined 3,255 participants. The results indicated that Ï = 0.4665 and credibility interval were 0.2023 < Ï < 0.7307. It can be inferred that there was a relationship between career decision making self-efficacy and career maturity.